2021
DOI: 10.1063/5.0038359
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal in-plane permittivity and ferroelectricity of confined water: From sub-nanometer channels to bulk

Abstract: Dielectric properties of nano-confined water are important in several areas of science, i.e. it is relevant in dielectric double layer that exist in practically all heterogeneous fluid-based system. Molecular dynamics simulations are used to predict the in-plane dielectric properties of confined water in planar channels of width ranging from sub-nanometer to bulk. Because of suppressed rotational degrees of freedom near the confining walls the dipole of the water molecules tend to be aligned parallel to the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…As an effective and powerful alternative tool, molecular dynamics (MD) simulation has presented excellent performance in the study of thermophysical properties of water at nanoscales, such as viscosity (Neek-Amal et al, 2016;Zhou et al, 2021), thermal conductivity (Zhao et al, 2020a;Zhao et al, 2020b), diffusion coefficient (Zhao et al, 2020c), and dielectric constant (Hamid et al, 2021). And it becomes a common sense that molecular behaviors of water under nanoconfinement deviate from bulk behaviors (Sofos et al, 2013;Sofos and Karakasidis, 2021) because of the large surface-to-volume ratio and the enhanced effects of surface properties including surface wettability and surface morphology (Shadloo-Jahromi et al, 2020;Shadloo-Jahromi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an effective and powerful alternative tool, molecular dynamics (MD) simulation has presented excellent performance in the study of thermophysical properties of water at nanoscales, such as viscosity (Neek-Amal et al, 2016;Zhou et al, 2021), thermal conductivity (Zhao et al, 2020a;Zhao et al, 2020b), diffusion coefficient (Zhao et al, 2020c), and dielectric constant (Hamid et al, 2021). And it becomes a common sense that molecular behaviors of water under nanoconfinement deviate from bulk behaviors (Sofos et al, 2013;Sofos and Karakasidis, 2021) because of the large surface-to-volume ratio and the enhanced effects of surface properties including surface wettability and surface morphology (Shadloo-Jahromi et al, 2020;Shadloo-Jahromi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…And it becomes a common sense that molecular behaviors of water under nanoconfinement deviate from bulk behaviors (Sofos et al, 2013;Sofos and Karakasidis, 2021) because of the large surface-to-volume ratio and the enhanced effects of surface properties including surface wettability and surface morphology (Shadloo-Jahromi et al, 2020;Shadloo-Jahromi et al, 2021). Thus, the thermophysical properties generally depend on the size of nanochannels or pores (Sofos et al, 2013;Zhao et al, 2020a;Zhao et al, 2020b;Zhao et al, 2020c;Hamid et al, 2021;Sofos and Karakasidis, 2021;Zhou et al, 2021). Studies on the specific heat capacity of water and other fluids using the MD method (Gautam et al, 2018;Alkhwaji et al, 2021) further demonstrated the potential of the MD method on the investigation of water at nanoscales.…”
Section: Introductionmentioning
confidence: 99%
“…Fluids under nanoconfinement are challenging to understand because they can show properties that are quite different compared to their bulk counterpart. For example, they form layers parallel to the confining surfaces, and, when the confinement width is ultrathin, the layers can solidify in peculiar structures . In the case of nanoconfined water, freezing can happen both above or below , the bulk melting temperature depending on the confining system.…”
mentioning
confidence: 99%
“…Nonetheless, it remains unresolved, as results are quantitatively in disagreement. Hamid et al . report a more pronounced increase of ε ∥ , which deviates from the bulk value for channel heights up to ≈100 nm.…”
Section: Resultsmentioning
confidence: 86%
“…Nonetheless, it remains unresolved, as results are quantitatively in disagreement. Hamid et al 42 report a more pronounced increase of ε ∥ , which deviates from the bulk value for channel heights up to ≈100 nm. Schlaich et al, 41 in contrast, report for soft polar surface confinement only a slight increase (≈ 10%) but only for channel heights below ≈0.5 nm.…”
Section: Resultsmentioning
confidence: 99%